Unlocking International Markets: The Impact of Digital Marketing and Supply Chain Adaptability on Jepara's Furniture Exports - Mariatus Sholikah; Mohammad Rifqy Roosdhani; Sisno Riyoko (Jurnal Bisnis dan Manajemen, 2025)
This study examines the effects of digital marketing and supply chain capability on export marketing performance among furniture exporters in Jepara, Indonesia, with networking and corporate reputation serving as mediating variables. The research addresses inconsistencies in previous empirical findings by analyzing how organizational capabilities are translated into performance outcomes within the context of small and medium-sized export-oriented enterprises. Using a quantitative explanatory research design, data were collected through closed-ended questionnaires distributed to 156 furniture exporting SMEs in Jepara Regency, selected using purposive sampling based on specific criteria and measured using a 10-point Likert scale. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software to assess the measurement model, structural relationships, and mediation effects. The findings indicate that supply chain capability, global market adaptability, networking, and corporate reputation have a positive and significant effect on export marketing performance. Digital marketing does not have a significant direct effect on marketing performance; however, it exerts a significant indirect effect through networking and corporate reputation. These results highlight the importance of relational and reputational mechanisms in transforming organizational capabilities into improved performance in international markets. The study suggests that exporters should integrate digital marketing initiatives with relationship-building and reputation management strategies, while policymakers should strengthen digital infrastructure and supply chain support to enhance the global competitiveness of Jepara’s furniture industry.